Ebony Jewelwing, Black-Winged Damselfly (suggested common names) Calopteryx maculata (Beauvois, 1807) (Insecta: Odonata: Calopterygidae) - Alfred Runkel; Nathan Burkett-Cadena; Andrea Lucky (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 4-page fact sheet that discusses the ebony jewelwing was written by Alfred Runkel, Nathan Burkett-Cadena, and Andrea Lucky, and published by the UF Entomology and Nematology Department, November 2017.